2017
DOI: 10.1111/1750-3841.13816
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Inhibitory Effect and Mechanism of Proanthocyanidins from Pyracantha fortuneana Fruit on α‐Glucosidase

Abstract: In this study, Pyracantha fortuneana fruit proanthocyanidins with a yield of 3.05% were identified for the first time as predominantly constituted of procyanidin with A-type and B-type linkage and coexistence of procyanidins glucoside. Proanthocyanidins from P. fortuneana fruit had higher anti-α-glucosidase activity value compared with positive control acarbose, which indicated that P. fortuneana fruit proanthocyanidins with a possibility to be used as novel natural antidiabetic agents in functional food indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…Li, a wild evergreen shrub or small arbour belonging to the Pyracantha of Osaceae apple subfamily, is mainly distributed in areas from eastern Asia to southern Europe. Pyracantha fortuneana fruit (PFF), as a new food resource, has become a research hotspot due to its rich nutrients and natural active ingredients, and it is even treated as a staple food in some areas in case of food shortage (Wei et al ., 2017; Wang et al ., 2019). However, most PFF are wild fruits, with several disadvantages for eating, such as small fruit size, rough and astringent taste, fresh fruit seasonality and intolerance to storage.…”
Section: Introductionmentioning
confidence: 99%
“…Li, a wild evergreen shrub or small arbour belonging to the Pyracantha of Osaceae apple subfamily, is mainly distributed in areas from eastern Asia to southern Europe. Pyracantha fortuneana fruit (PFF), as a new food resource, has become a research hotspot due to its rich nutrients and natural active ingredients, and it is even treated as a staple food in some areas in case of food shortage (Wei et al ., 2017; Wang et al ., 2019). However, most PFF are wild fruits, with several disadvantages for eating, such as small fruit size, rough and astringent taste, fresh fruit seasonality and intolerance to storage.…”
Section: Introductionmentioning
confidence: 99%
“…Pyracantha fortuneana fruit (PFF) is a fruit which is rich in proanthocyanin. The results of the research indicated that PFF inhibited αglucosidase in a non-competitive type with the IC 50 value of 0.15 μg/ml (Wei et al, 2017). The study also demonstrated the inhibitory mechanism of proanthocyanins on α-glucosidase.…”
Section: Antidiabetic Activity Of Dietary Fruits In Invitro Studiesmentioning
confidence: 75%
“…For instance Sarcopoterium spinosum, Japanese apricot, Ficus deltoidea, Passiflora ligularis, Persea Americana, Rosa canina, Vaccinium myrtillus, Terminalia catappa L., Myristica fragrans, Pimenta dioica, Momordica charantia, Sarcopoterium spinosum, Mango, Pyracantha fortuneana, Chrysophyllum cainito L., Pometia pinnata, Malus communis L., Empetrum nigrum L., Momordica charantia, Zizyphus lotus, Xylopia aethiopica, Morinda Citrifolia L., Malus communis L., Coriandrum sativum L., Juglans regia L., Sorbus umbellate, Fritsch var. Cretica, Schneider and encapsulated Citrus limon Osbeck were reported for their inhibitory activity on α-amylase and αglucosidase enzymes (Smirin et al, 2010;Park et al, 2012;Misbah et al, 2013;Saravanan and Parimelazhagan, 2014;Oboh et al, 2014;Asghari et al, 2015;Guder et al, 2015;Adefegha et al, 2016;Loizzo et al, 2016;Khatib et al, 2017;Elyasiyan et al, 2017;Sekar et al, 2017;Putri et al, 2017;Wei et al, 2017;Doan et al, 2018;Sukiman et al, 2018;Yegin et al, 2018;Hyun and Kim 2018;Hwang, 2018;Yegin et al, 2018;Deniz et al, 2018;Raimov and Fakir., 2018;Incegul et al, 2018;Marmouzi et al, 2019;Mohammed et al, 2019;Simomara et al, 2019). Juniperus communis, Eugenia jambolana, Foeniculum vulgare, Secale cereale L., Carum carvi and Capparis spinosa L., Rosa canina L., Rhus coriaria L., Phaleria macrocarpa, Persea americana Mil., Pithecellobium dulcee Benth, Carum carvi, Vacciniummyrtillus, Backhousia citriodora oil, Vanilla planifolia Andrews were analyzed for their antidiabetic effects using STZ or alloxan induced rats (Medina et al, 1993;Kelkar and Kaklij (1997);Ozbek, 2002;Ozbek et al, 2002;Eddouks et al, 2004;Orhan et al, 2009;…”
Section: Introductionmentioning
confidence: 99%
“…The α-glucosidase is another digestive enzyme; it has been suggested that caffeic acid and procyanidin B dimer compounds insertion alters catalytic configuration reducing therefore its affinity to bind to the substrate (Wei et al, 2017). The caffeic acid and its derivatives, as 5-caffeoylquinic acid, have been reported as α-glucosidase inhibitors (Kalita et al, 2018).…”
Section: Introductionmentioning
confidence: 99%